Sensitivity of the Winter-Kennedy method to different guide vane openings on an axial machine. (August 2019) - Baidar, Binaya; Nicolle, Jonathan; Gandhi, Bhupendra K.; Cervantes, Michel J.
Abstract: This work studies the effects of guide vane openings (GVOs) on the Winter-Kennedy (WK) flow measurement method using CFD. The dependence of the WK coefficient with GVOs and its physical mechanism are presented. Although the WK method is reported to be sensitive to different factors including GVO, it is still unclear to which extent the GVO can be changed without modifying the WK coefficient significantly and the mechanism leading to such modification, if any. A numerical model of a Kaplan model turbine with a semi-spiral casing is developed and used to such purpose. Previously conducted experiments on the model turbine are used to validate the numerical results. The magnitude and behavior of the secondary flow are investigated together with the WK coefficients. The GVO is found to have an impact on the WK method, and the impact increases with the GVOs as the flow structure change. A suitable location to minimize the impact of the GVO is suggested. Furthermore, the theoretical WK constant with a suitable location and configuration are also presented; this can be useful in the absence of the measured WK coefficient. Highlights: Sensitivity of the Winter-Kennedy method correlates with the secondary flow structure. Location to minimize the impact of guide vane opening is proposed. Theoretical Winter-Kennedy constant is derived.